Python NetWorkSpaces - Bjornson, Robert; Carriero, Nicholas; Weston, Stephen (Dr. Dobb's Journal, 2007)
Many developers work with newer dynamic languages like Python and R. To meet the needs of these users, we've developed a Python-based coordination system called "NetWorkSpaces" (NWS) that is easy to learn, accessible via almost all development environments (including R, Java, octave, Python, Perl, and Ruby), and déployable on ad hoc collections of spare CPUs. The advantages this neutrality offers include: * ISfWS coordination patterns and idioms can be recycled from one language environment to the next. * NWS can be used to coordinate heterogeneous ensembles of code written in different languages. [...] Python NWS can automatically handle composite data structures: * from nws.client import NetWorkSpace * ws=NetWorkSpace('test') * 1=['a','b','b'] * t=(l,2,3) *d={ ' list ' : 1, ' tuple ' :t} * ws. store ('diet example', d) * ws.fetchf'dict example' {'list': l'a', 'b', 'c', 'tuple': (1, 2, 3)} Finally, ASCII strings used as values are treated in a special way (they are not subject to the client language serialization protocol) that makes it possible for them to be exchanged across client languages.